2014
DOI: 10.1049/iet-com.2013.0944
|View full text |Cite
|
Sign up to set email alerts
|

Two‐level scheme to maximise the number of guaranteed users in downlink femtocell networks

Abstract: In this study, the authors study the downlink resource allocation optimisation in femtocell networks, to maximise the number of guaranteed users whose data rate requirements are fully met. The spectral access of femtocell networks is based on orthogonal frequency division multiple access. In their work, two challenges are solved. The first is the intractable inter-cell interference coordination brought about by the transmission delay in backhaul connections, and the second is the incorporation of physical inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…7). Our dissolution result is similar to the reports by Xi et al 37) and Yang et al 38) where they reported the dissolutions of OA rapidly released from their L-SEDDS to be 75% and 85%, respectively. Thus, our S-SEDDS prepared with mannitol had a comparable in vitro dissolution of the OA drug to L-SEDDS.…”
Section: )supporting
confidence: 92%
See 1 more Smart Citation
“…7). Our dissolution result is similar to the reports by Xi et al 37) and Yang et al 38) where they reported the dissolutions of OA rapidly released from their L-SEDDS to be 75% and 85%, respectively. Thus, our S-SEDDS prepared with mannitol had a comparable in vitro dissolution of the OA drug to L-SEDDS.…”
Section: )supporting
confidence: 92%
“…[2][3][4][5] In China, OA has been used as an oral drug for human liver disorders in a conventional tablet or capsule formulation. 6,7) However, OA has various disadvantages such as poor water solubility (4.61 µg/ mL) and low dissolution rate, thus leading to low absorption and bioavailability. 8,9) Due to these limitations, chemically modified derivatives have been developed to improve water solubility.…”
mentioning
confidence: 99%
“…In this case a distinction of a user which can be found in the inner or outer zone of the cell. In an OFDMA based network, we assume the user as x in a base station s on subcarrier c, the related SNIR can be calculated using Equation 1 (Chung et al, 2014;Hindia et al 2014;Wang et al 2014…”
Section: Methods and System Modelmentioning
confidence: 99%
“…In LTE, each OFDMA traffic channel is solely allocated to one individual, which provides the end-user frequency with a high degree of reliability and flexibility (Zhao et al, 2012). The device efficiency is significantly degraded by the Inter-cell Interference (ICI) dependent on a multi cell LTE OFDMA-related network because of the same frequency reuse and interference by the co-channel (CCI) when more than one radio transmitters use the same frequency (Chung et al, 2014;Elayoubi et al, 2008;Hindia et al, 2014;Mannweiler et al, 2020;Wang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%